Сlinical case of focal alopecia in a child with atopy - A. A. Barilo (Medicinskaâ Immunologiâ, 2021)
Alopecia areata is a common inflammatory immune-mediated disorder in which autoimmune response is triggered against hair follicles, thus leading to non-scarring hair loss on the scalp, face and other parts of the skin. Despite numerous studies concerning this issue, today there is no consensus on the etiology and pathogenesis of focal alopecia. In the literature, special attention is paid to association of focal alopecia with autoimmune diseases, such as rheumatoid arthritis, celiac disease, type 1 diabetes, psoriasis, autoimmune thyroiditis, vitiligo. Recent studies have identified the association of focal alopecia with atopic diseases (allergic rhinitis, bronchial asthma, atopic dermatitis) and the early debut of severe forms of hair loss. The aim of this study was to present a clinical case of focal alopecia in an 8-year-old girl with atopic bronchial asthma and seasonal allergic rhinitis. As based on detection of eosinophilia in peripheral blood and a high concentration of total IgE in serum, one may assume that atopic alopecia is the cause of focal hair losses in a child with atopy. The patient underwent skin prick testing, in order to determine sensitization for food components, pollen and fungal allergens. As a result of skin testing, a hyperergic reaction (> 15 mm in diameter) to tree pollen was revealed, a positive response (6-9 mm) to oatmeal, a weakly positive reaction (3-5 mm) to whole chicken egg, carrots, tomato, apple, pear, pollen of meadow, cereal, weed grasses was also revealed. With regard of these allergological data, an individual diet was recommended with the elimination of causally significant allergens (including those eliciting weakly positive reactions), external treatment, i.e., topical calcineurin inhibitors administered for 1 month. One month later, an improvement of the pathological process was registered, and 6 months from the start of therapy, complete restoration of hair follicles was noted in the focus of alopecia. The patient was monitored for a year, no complaints of hair loss were noted. The positive effect of elimination against the background of the appropriate elimination diet with respect to causally significant allergens, was also noted when treating her for respiratory allergy, i.e., the patient did not have seasonal manifestations of hay fever over the next pollination period. This clinical case is demonstrated in order to draw special attention of dermatologists, allergologists, immunologists, general practitioners to the issues of focal alopecia in children against the background of typical allergic diseases.